Curriculum Reconstruction: Alignment of Profile, Body of Knowledge, and Learning Outcomes of the Indonesian Islamic Education Study Program - Eva Latipah; Hasan, Noorhaidi; Mohamad Agung Rokhimawan (Jurnal Pendidikan Agama Islam, 2023)
Purpose – The misalignment between the profile with the body of knowledge (BoK) and the graduates’ learning outcomes (LO) of the PAI Study Program has caused the unclear educational objectives of the PAI study program, requiring the reconstruction of the PAI curriculum. This study aims to examine the reconstruction process of the PAI curriculum including the Profile, BoK, and LO of the PAI. Design/methods/approach –The research was conducted qualitatively using survey, interview, and documentation methods packaged in seminars, guest lectures, workshops, and Focus Group Discussions. The subjects in this study were 83 PAI Study Program managers from Sumatra, Jakarta and Jabodetabek, DIY and Central Java, East Java, and the Eastern regions; the interviews were carried out with 15 study program managers. The obtained data was processed through the stages of reduction, display, and interpretation. Findings – The results showed: 1) there are 6 profiles of Indonesian PAI after being reduced from 51 profiles, namely PAI teachers in schools/madrasahs, educational consultants, research assistants, administrators of educational institutions, Da’i/muballigh, and edupreneurs, 2) PAI’s Body of Knowledge consists of four scientific families: PAI science (what to teach), teaching science (how to teach), education and psychology (how to discipline), Research methodology, philosophy, language, technology, edupreneur (how to produce), 3) Graduate learning outcomes include in-depth mastery of PAI science, teaching, pedagogic, and PAI development, as well as how to teach PAI science effectively. Research implications/limitations – This research has implications for the importance of preparing graduate profiles based on tracer studies, rather than based on ‘personal wishes’; and Learning outcomes must be adjusted to the standardized BoK of the Study Program. Originality/value – the importance of profile mapping based on tracer studies, the significance of PAI’s body of knowledge in achieving PAI goals, and the importance of graduate learning outcomes for the expertise of PAI graduates.